Students’ and Teacher’s Views on the Effectiveness of Multiple Intelligences-Assisted Layered Curriculum in the Social Studies Course - Bilgili, Ali Sinan; Gömleksiz, Mehmet Nuri; Öner, Ümmühan (My University, 2020)
The aim of this study is to determine students’ and Social Studies teacher’s viewson the effectiveness of multiple intelligences-assisted layered curriculum. Studygroup includes 14 7th grade students and one Social Studies teacher at a primaryschool in Elazığ city center during 2010-2011 academic year. The research wasconducted based on the “case study\" research design, one of the qualitativeresearch designs. As data collecting tool, student and teacher interview form andobservation form consisting of open-ended questions were used. Content analysiswas used to analyse the data. It was found out that the useful aspects of multipleintelligences-assisted layered curriculum were ‘helping students to learn’,‘repetition’, ‘motivating to do research’, ‘active participation in class’ and‘increasing students’ interest’. When choosing an activity, the students paidattention to whether the activities were ‘difficult’, ‘easy’, ‘helpful for students tolearn’, ‘interesting’ and ‘related to drawing’. In the process of implementation ofthe multiple intelligences-assisted layered curriculum, it was found out that thestudents had difficulty in ‘writing story’, ‘writing essay’, ‘writing poem’, ‘solvingtest’, ‘drawing map’, and ‘selecting activity’
Keywords: Eğitim; Eğitim Araştırmaları